FILOSOFI MANAJEMEN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DI PR. GUDANG JAYA PRIMA - Siti maghfirotul ummah; Alfin aulia rahman; Saadatul husna; Wahyu sugeng; Abdul wahid mahsuni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the influence of work culture on employee performance, in this study resulted in 12.6% of the influence of work culture on improving employee performance. This study used a sample of 31 employees using primary data taken from the results of questionnaire data that had been carried out by PR Gudang Jaya Prima employees, processing of questionnaire data was carried out using the help of the SPSS 25 application for windows. The results of this study show that work culture has a positive influence on employee performance